Upaya Meningkatkan Perkembangan Motorik Kasar Anak Melalui Permainan Tradisional Benteng-Bentengan Pada Kelompok B di PAUD As-Syifa’ Turun Tangis - Rachmi, Evanalie; Karlina, Novi; Subyanto, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This collaborative action research aims to investigate efforts to enhance gross motor skills in children through traditional fort-playing games in the B group of PAUD AS-Syifa’ Turun Tangis. Data collection techniques employed were observation and documentation comprising notes, drawings, and RPPH (Lesson Plan Implementation Records). Data analysis was conducted descriptively and qualitatively. The research's success criteria were achieving an 80% improvement in children's gross motor skills, categorized as 'very good'. Results indicate a notable improvement in children's gross motor skills through traditional fort-playing games. Initial observations showed a 25% increase in gross motor skills development during the first cycle but did not meet the success criteria. By the second cycle, there was a significant improvement to 81%, meeting the target criteria excellently. The study was successful, demonstrating an 81% improvement in 13 children achieving 'Very Good Development' (BSB) status in cycle II. This underscores the effectiveness of traditional fort-playing games in significantly enhancing gross motor skills development among the B group of PAUD AS-Syifa’ Turun Tangis.